2017
DOI: 10.7717/peerj.3525
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized zeolites as modulators of thiacloprid toxicity onChironomus riparius

Abstract: This study investigated whether zeolites of different size (Y30 (nano-sized) and H-Beta(OH)-III (forming large aggregates/agglomerates composed of 50 nm small primary particles)) exerted acute toxicity on larvae of the non-biting midge, Chironomus riparius, and whether such zeolites are able to modulate the toxicity of a common insecticide, thiacloprid, by means of adsorption of a dissolved toxicant. We conducted acute toxicity tests with fourth instar larvae of C. riparius. In these tests, larvae were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The external surface charge of the zeolite nanoparticles in particular has been shown to play an important role in many interactions . For instance, nanosized zeolites have been used as multifunctional nanocarriers to deliver organic molecules into living cells where the drug of interest is attached to the external surfaces. …”
Section: Preparation and Crystal Characterizationmentioning
confidence: 99%
“…The external surface charge of the zeolite nanoparticles in particular has been shown to play an important role in many interactions . For instance, nanosized zeolites have been used as multifunctional nanocarriers to deliver organic molecules into living cells where the drug of interest is attached to the external surfaces. …”
Section: Preparation and Crystal Characterizationmentioning
confidence: 99%
“…There is a gap in the datasets and predictive models, which might cause obstacles in the toxicity assessment of nano-mixtures by using the in silico approach. To provide readers with a picture of the currently available datasets and predictive models of nano-mixture toxicity, in this review, we collected and curated 183 studies [ 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Introductionmentioning
confidence: 99%
“…The zeolites were also reported applied in controlling the insect pest Chironomus riparius. It was found that zeolite concentration determined the effectiveness of their control (Lorenz et al, 2017). In addition, it is also expected that the delivery system (zeolite) is in synergy to support the virus-infected insect target.…”
Section: Introductionmentioning
confidence: 99%